Methane Monooxygenase Gene Transcripts as Quantitative Biomarkers of Methanotrophic Activity in Methylosinus trichosporium OB3b - Tentori, Egidio F. (Appl Environ Microbiol, 2020)
Methanotrophic microorganisms are characterized by their ability to oxidize methane. Globally they have a significant impact on methane emissions by attenuating net methane fluxes to the atmosphere in natural and engineered systems, though the populations are dynamic in their activity level in soils and waters. Methanotrophs oxidize methane using methane monooxygenase (MMO) enzymes, and selected subunit genes of the most common MMOs, specifically pmoA and mmoX, are used as biomarkers for the presence and abundance of populations of bacterial methanotrophs. The relative expression of these biomarker genes is dependent on copper-to-biomass ratios. Empirically derived quantitative relationships between methane oxidation biomarker transcript amounts and methanotrophic activity could facilitate determination of methane oxidation rates. In this study, pure cultures of a model type II methanotroph, Methylosinus trichosporium OB3b, were grown in hollow-fiber membrane bioreactors (HFMBR) under different steady-state methane oxidation conditions. Methanotroph biomass (DNA based) and methane oxidation biomarker mRNA transcript amounts were determined using quantitative PCR (qPCR) and reverse transcription-PCR (RT-qPCR), respectively. Under both copper-present and copper-limited conditions, per-cell pmoA mRNA transcript levels positively correlated with measured per-cell methane oxidation rates across 3 orders of magnitude. These correlations, if maintained across different methanotrophs, could prove valuable for inferring in situ oxidation rates of methanotrophs and understanding the dynamics of their impact on net methane emissions. IMPORTANCE Methanotrophs are naturally occurring microorganisms capable of oxidizing methane and have an impact on global net methane emissions. The genes pmoA and mmoX are used as biomarkers for bacterial methanotrophs. Quantitative relationships between transcript amounts of these genes and methane oxidation rates could facilitate estimation of methanotrophic activity. In this study, a strong correlation was observed between per-cell pmoA transcript levels and per-cell methane oxidation rates for pure cultures of the aerobic methanotroph M. trichosporium OB3b grown in bioreactors. If similar relationships exist across different methanotrophs, they could prove valuable for inferring in situ oxidation rates of methanotrophs and better understanding their impact on net methane emissions.